Packaging Accessibility: Developing a Comparison Tool for Structural Designs. (September 2022) - Conn, Paula; Abisla, Richard; Batra, Sanjay
In this work, we synthesize 27 emerging research studies and standards to develop a resource that highlights accessibility risks of new design concepts. Prior studies have identified key factors that influence packaging accessibility: we summarize major themes and validate our findings through a Human Factors usability study. Results suggest that the design comparison tool can contribute to more accessible packaging, yielding a statistically significant difference in participants' preference rankings. While existing methodologies evaluate a package's accessibility at the final stages of the development process, this work suggests that usability problems can be surfaced as early as design conceptualization.